A nearly uniform distributional pattern of heterotrophic bacteria in the Mariana Trench interior. (December 2018) - Tian, Jiwei; Fan, Lu; Liu, Haodong; Liu, Jiwen; Li, Yi; Qin, Qilong; Gong, Zheng; Chen, Hongtao; Sun, Zhongbin; Zou, Li; Wang, Xuchen; Xu, Hongzhou; et al.
Abstract: The uniqueness of hadal trench environment and its potential role in global carbon sequestration allows for a detailed study of microbially driven carbon cycle of the trench system. Limited studies on microbiology by far have suggested that the hadal-sphere generally hosts a heterotrophic microbial community that is mostly fed by surface-sinking organic matter or re-suspended and laterally transported organic matter from sediments. However, temporal dynamics in trench microbial community in connection to surface and sediment organic carbon exports is still beyond our knowledge. In this study, we conducted vertical sampling and analysis of the microbial community from the epipelagic zone down to the hadal zone at the Mariana Trench. 16S rRNA gene composition showed high variations at the first 1000 m below surface (mbs); however, a nearly uniform microbial community composition (Jaccard dissimilarity less than 73%) was observed below 1000 mbs and down into the bottom of the trench. The deep-sea bacteria were generally chemoheterotrophs characterized by Erythrobacter, Rhodovulum, Alteromonas, some Marinobacter, etc., which were also present at the ocean surface. Several deep-sea-enriched but surface-depleted bacteria include Glaciecola, Oceanicola and Oleibacter were potential degraders of large organic polymers. In spite of consistent community composition, enhanced chromophoric dissolved organic matter proportions in the hadal zone of the trench might imply intensified microbial activity compared to the water column above. These observations suggest an unusual transitory state of the Mariana Trench water columns and extend our understanding of the dynamics of the hadal microbial community. Highlights: Abundant bacterial heterotrophs were detected below 1000 m of the Mariana Trench. Nearly uniformed microbial composition in the hadal zone and the overlain deep ocean. Community difference between differently-sized aggregates was insignificant. DOC variation suggests active microbial respiration in the hadal zone. Some deep-sea-enriched bacteria are potential degraders of large organic polymers.